2014
DOI: 10.1007/978-3-662-43376-8_6
|View full text |Cite
|
Sign up to set email alerts
|

LINC: A Compact Yet Powerful Coordination Environment

Abstract: Abstract. This paper presents LINC, a coordination programming environment. It is an evolution of earlier middlewares (the Coordination Language Facility (CLF) and Stitch). The aim is to provide a more flexible and expressive language correcting several of their limitations and an improved run-time environment. LINC provides a compact yet powerful coordination language and an optimised run-time which executes rules. This paper describes the intrinsic properties brought by the LINC environment and how it helps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…It shows the averages of latency time of different scenarios. Each scenario consists of the execution during 2 minutes of a specific number of rules between (1,10,30,50,70,90,100,200,300,400), and the generation of a number of events for each rule among (5,10,11,15,20,30,100,200) events per second. It is found that for all sets of rules, the delay is negligible when the number of events/second are less than or equal to 11.…”
Section: Resultsmentioning
confidence: 99%
“…It shows the averages of latency time of different scenarios. Each scenario consists of the execution during 2 minutes of a specific number of rules between (1,10,30,50,70,90,100,200,300,400), and the generation of a number of events for each rule among (5,10,11,15,20,30,100,200) events per second. It is found that for all sets of rules, the delay is negligible when the number of events/second are less than or equal to 11.…”
Section: Resultsmentioning
confidence: 99%
“…LINC [17] is a rule based middleware used to develop and deploy distributed applications. It has been used in several domains such as building automation [20][21][22] and wireless sensor networks [23][24][25].…”
Section: Linc Middlewarementioning
confidence: 99%
“…The framework is based on the combination of a rule based transactional middleware (LINC [17]) and a reactive language (Heptagon/BZR [18]). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the core tools, add-on services provide site-specific services covering modeling and decision support (Figure 1b). LINC/RTU: At the lowest level, the building and data heterogeneity is hidden by LINC [1] and the RTU (ACE1000 Remote Terminal Unit) (https://www.motorolasolutions.com/en_us/products/ industrial-internet-of-things/scada/ace1000-rtu.html). LINC provides a universal abstraction layer based on tuple spaces.…”
Section: Topas Platformmentioning
confidence: 99%